ON THE SELECTION OF DRUGS DOSAGE REGIMEN - E. N. Bochanova (Столичная издательская компания, 2015)
A complex system of hemostasis regulation, insufficient data on drugs pharmacokinetics, multiple factors effecting treatment, including patient's adherence to therapy, that can lead to the need for the dosage regimen specification are presented.